Los zapaticos de rosa - Martí, José, 1853-1895 (Colección Rascacielos., 1997)
In this poem, young Pilar, adorned with feathered-hat and pink shoes, accompanies her mother to the beach. Pilar encounters a poor woman with a sickly child and gives the child her cherished shoes.